Adiekcje we współczesnych polskich przekładach Listu do Filemona - Kubski, Grzegorz (Poznańskie Studia Teologiczne, 2020)
A broadly understood concept of adjection used in rhetoric comprises various types of verbal and content references. This figure of speech plays an important role in the texts of the Holy Scripture as it shapes the literary construction of the world portrayed by the hagiographers and in consequence bears an impact on the message that they convey. New Bible translations into Polish usually focus on the communicative clarity of the vocabulary chosen, and are less frequently concerned with harmonizing the different levels of the text. The present paper compares eight contemporary Polish translations of the Letter to Philemon together with accompanying commentaries. Among other things, attention is drawn to such elements as the deployment of the etymology of the name Onesi- mus and its connection with the word Christos, the recurrence of the concept of “good”, emphasis on or omission of the connotations of the theme of fight. The interpretations of verses 1, 9, 10 and 14 are set apart since contain metaphors or metonymy. Respect for or reduction of the semantic function of the anaphora and epiphora is examined. The translators of the Letter to Philemon, com- pared to the translators of other books of the Bible, showed greater appreciation, though in varying degrees, of the meaning-formation value of adjection. Perhaps this is due to the shortness of this piece of writing by St. Paul, as fewer textual elements are easier to harmonize.